Investigating whether executive functioning, working memory capacity, & long-term memory can be improved by cognitive training - Lim, Ming Ze (2016)
Previous research showed improved working memory through cognitive training. However, comparatively little is known about whether long-term memory can be improved by such training. Several cognitive processes, including working memory and executive function, subserve long-term memory functioning. Thus, if the cognitive processes that subserve long-term memory could be improved via training, these should then lead to broad improvements in learning and episodic memory. To test for these predictions, a pilot study was first conducted to examine whether training using three different cognitive training conditions would improve performance in tasks measuring working memory, executive functions, reading comprehension, and long-term memory for text information respectively. Participants were assigned to one of three possible training conditions (dual n-back training, meditation training, and practicing retrieval) over 20 daily sessions. Preliminary data suggested that mindfulness and retrieval practice could lead to changes that improved participants' working memory capacity and reading comprehension. The pilot study also suggested ways to improve participants' training experiences and adherence. Subsequently, a second study was conducted by incorporating modifications to the training protocols and with a reduction of training duration (i.e., from 20 daily sessions to 14 daily sessions). Paired-sample t-tests indicated that two training regimes (i.e., daily meditation training and practicing retrieval) led to changes that improve participants’ ability to store and retrieve episodic information formed while reading text passages. Also, only the meditation group improved on working memory capacity. This thesis concluded that certain training programs could work in improving various aspects of cognition, as well as discussing the possible mechanisms and accounts for training-induced transfers.